The states of public opinion on the environment. Issue 2 (3rd March 2016) - Fowler, Luke
ABSTRACT: State-level public opinion on the environment within the US is examined, using data from the General Social Survey (GSS) from 2000 to 2010. A Multilevel Regression and Post-Stratification (MRP) approach is taken to estimate three different survey items on environmental issues at the US state level. This allows for a comparable understanding of state-level public opinion on environmental issues, which is then connected to economic, environmental, and political conditions, and representation in policy making. The findings indicate the MRP technique is a sophisticated way to make accurate estimations of state-level public opinion, and those estimates provide further insight into the shaping of public opinion and public policy.